Combined Effect of Lentinan and Cisplatin on Cytokines IL-6, TNF-α, and TGF-β in Tumor Therapy - Xu-dong Liu; Min Li; Wan-xiang Li; Qing-yu Wang; Hong-xia Zhang (International Journal of Polymer Science)
Lentinan is a biologically active ingredient isolated from the fruiting body of Lentinula edodes (shiitake) and has antitumor properties. Cytokines, at the same time, are a key factor in regulating immune responses in physiological and pathological states. Many cytokines have shown positive effect on different malignancies in clinical trials. Studies have shown that such cytokines as IL6, TNF-α, and TGF-β play a quite important role in the formation of tumor microenvironment. In this study, we investigated the antitumor effect of combined medication of lentinan and cisplatin, another antitumor drug, and its impact on cytokines IL-6, TNF-α, and TGF-β in the treatment of tumor. The results showed that lentinan enhanced the cytotoxic effect of cisplatin on tumor cells. Furthermore, it was proved that the combined treatment of lentinan and cisplatin enhanced the inhibitory effect of cisplatin on the expression of IL-6, TNF- α, TGF-β and tumor growth in mice bearing human ovarian cancer xenograft, human prostate tumor xenograft, and human non-small cell lung cancer xenograft.